2007
DOI: 10.1590/s0101-20612007000400021
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de compostos nitrogenados presentes em farelos fermentados em estado sólido

Abstract: Farelo de arroz desengordurado e farelo de trigo foram submetidos à fermentação em estado sólido pelos fungos Rhizopus sp. e Aspergillus oryzae, visando a obtenção de um produto enriquecido em proteínas, reaproveitando um subproduto da indústria beneficiadora de cereais. Os farelos fermentados obtidos foram caracterizados quanto aos seus compostos nitrogenados. Foi determinado o conteúdo protéico, de aminoácidos totais e digeríveis e de metionina disponível. Os maiores aumentos nos teores protéicos dos farelos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 5 publications
2
18
0
3
Order By: Relevance
“…The lipid content of rice bran was 15.2% and after 48 h of fermentation, there was a decrease due its use for the mycelial synthesis. The same behavior was mentioned by Oliveira et al (2010) using rice bran as substrate during SSF with R. oryzae and by Silveira and Badiale-Furlong (2007), using defatted rice bran and wheat bran as substrates for Rhizopus sp and Aspergillus oryzae cultivation. According to Griffin (1993), nutrients in the substrate are used for the fungus cell wall production; consequently there is a decrease in polysaccharides in the substrate.…”
Section: Antioxidant Activity Of the Phenolic Extractssupporting
confidence: 72%
See 1 more Smart Citation
“…The lipid content of rice bran was 15.2% and after 48 h of fermentation, there was a decrease due its use for the mycelial synthesis. The same behavior was mentioned by Oliveira et al (2010) using rice bran as substrate during SSF with R. oryzae and by Silveira and Badiale-Furlong (2007), using defatted rice bran and wheat bran as substrates for Rhizopus sp and Aspergillus oryzae cultivation. According to Griffin (1993), nutrients in the substrate are used for the fungus cell wall production; consequently there is a decrease in polysaccharides in the substrate.…”
Section: Antioxidant Activity Of the Phenolic Extractssupporting
confidence: 72%
“…This difference could be related to the fact that the authors used defatted rice bran as substrate. The relevant increase in protein content and in the phenolic compounds antioxidant activity during fermentation have also been reported by Silveira and Badiale-Furlong (2007) and Oliveira et al (2010), guiding the interest in extracting both the components to apply in food formulations. Table 2 presents the protein solubilization and precipitation percentage from bran and fermented bran in the isoelectric point and with acetone (1:3).…”
Section: Antioxidant Activity Of the Phenolic Extractsmentioning
confidence: 55%
“…Such alteration was not expected, considering that their solubility was increased. Using similar fermentation conditions, Silveira et al (2003) found a reduction of 59% in the fermented wheat bran digestibility when Rhizopus sp. was used, which could be explained by the high chitin contents in the fungal biomass (Than and Nout, 2002).…”
Section: Bran Characterizationmentioning
confidence: 95%
“…Media were adjusted to 50% moisture and pH 5 by addition of HCl (400mM). Substrates were inoculated using 4 x 10 6 spores/g of medium (Silveira et al, 2003;Costa et al, 1998). Fermentation was carried out in trays in a 1 cm thickness layer.…”
Section: Bran Characterizationmentioning
confidence: 99%
“…These residues can be availed for SSB, adding value to the formed product. The action of fungi on solid waste can turn it into a material rich in proteins though the transformation of the medium composition [6].…”
Section: Introductionmentioning
confidence: 99%